Clinical, Bronchographic, Radiological, and Physiological Observations in Ten Cases of Asbestosis - Leathart, G. L. (1960)
Ten cases of asbestosis (eight male, two female), aged 45-65 years have been kept under observation for periods of up to eight years. Bronchiectasis was demonstrated bronchographically in six cases. Clubbing of the fingers and coarse crepitations appeared to be signs of bronchiectasis rather than of uncomplicated asbestosis. It is suggested that the prevalence of bronchiectasis is higher than has been reported previously because the patients survived longer. The radiological findings are tabulated and compared with previous descriptions. In these subjects there was no relationship between radiological and clinical state. Nine patients eventually showed clinical deterioration and it often proceeded rapidly. The radiograph however, usually remained unaltered. Pulmonary function tests, including diffusing capacity, arterial blood analysis and estimation of mechanical properties of the lung, were carried out in these 10 cases, and in 11 asbestos workers (aged 35-64 years) without radiological abnormality. The steady state diffusing capacity for carbon monoxide (Dco) at rest was lower in asbestosis than in the control subjects. The pulmonary compliance was remarkably low in asbestosis and related fairly closely to the vital capacity. The maximum voluntary ventilation was also low and was related to increased pulmonary resistance but it cannot be said whether this is in the airways or in the lung tissue. Indirect evidence of inequalities of ventilation/perfusion ratio was obtained in most cases. There is no convincing evidence that pulmonary fibrosis occurs without radiological abnormality, but a defect of diffusion may occur. There is no test of pulmonary function which is diagnostic, but a low pulmonary compliance, especially if combined with a low diffusing capacity, is confirmatory. It is suggested that the demonstration of a progressive decline in vital capacity, or in diffusing capacity, may enable a diagnosis of asbestosis to be made before radiological abnormality has appeared, but this point has not been proved.